Identification of Mutant Versions of the Spt16 Histone Chaperone That Are Defective for Transcription-Coupled Nucleosome Occupancy in Saccharomyces cerevisiae - Hainer, Sarah J. (Genetics Society of America, 2012)
The highly conserved FACT (Facilitates Chromatin Transactions) complex performs essential functions in eukaryotic cells through the reorganization of nucleosomes. During transcription, FACT reorganizes nucleosomes to allow passage of RNA Polymerase II and then assists in restoring these nucleosomes after RNA Polymerase II has passed. We have previously shown, consistent with this function, that Spt16 facilitates repression of the Saccharomyces cerevisiae SER3 gene by maintaining nucleosome occupancy over the promoter of this gene as a consequence of intergenic transcription of SRG1 noncoding DNA. In this study, we report the results of a genetic screen to identify mutations in SPT16 that derepress SER3. Twenty-five spt16 mutant alleles were found to derepress SER3 without causing significant reductions in either SRG1 RNA levels or Spt16 protein levels. Additional phenotypic assays indicate that these mutants have general transcription defects related to altered chromatin structure. Our analyses of a subset of these spt16 mutants reveal defects in SRG1 transcription-coupled nucleosome occupancy over the SER3 promoter. We provide evidence that these mutants broadly impair transcription-coupled nucleosome occupancy at highly transcribed genes but not at lowly transcribed genes. Finally, we show that one consequence shared by these mutations is the reduced binding of mutant Spt16 proteins across SRG1 and other highly transcribed genes. Taken together, our results highlight an important role for Spt16 in orchestrating transcription-coupled nucleosome assembly at highly transcribed regions of the genome, possibly by facilitating the association of Spt16 during this process.